The Use of Computer-Mediated Communication (CMC) in Distance Learning During Covid-19 Period The Case of Second Year Students at the Department of English, Laghouat University - Meddah,Yacine; Charfaoui, Samia (University of Ammar Theledji -Laghouat, 2021)
The Covid 19 pandemic has dramatically affected all aspects of society and made a huge change in the teaching-learning process. To suppress the spread of this contagious disease, restricted laws have been issued such as social distancing, and home quarantine. As a consequence, the ministry of higher education has not only decided to shut down the educational institutions, but also ensuring that education will continue by using an alternative to the traditional method of learning which is virtual education. This change, however, required the use of Information and Communications Technology (ICT) such as Computer-Mediated Communication (CMC) to maintain the social interaction between teachers and their students. It was hoped that the use of CMC in distance learning would be efficient to carry out the learning process. Therefore, the aim of the present study is to investigate learners’ attitudes towards the use of CMC during distance learning in the university of Ammar Thelidji, Laghouat. To achieve our goal, Master Two learners from the English department of the university of Ammar Thelidji, Laghouat participated in this study. The research used a descriptive research method to achieve its purpose using a student questionnaire. The results obtained indicate that learners seemed to have negative experiences towards utilizing CMC in remote learning. Yet, they believed that the effective use of CMC and the integration of its tools would facilitate and improve remote learning in our department. Based on the findings, some suggestions were offered to the university, teachers, and further research in order to treat and ameliorate the current state of distance learning